Current Emergency Preparedness Resources and Capabilities Among Academic Health Systems in the United States. (21st February 2018) - Biddinger, Paul D.; Reisman, David; Seger, Robert F.; Prestipino, Ann L.; Sinclair, Julia; Wante, Barry; Goralnick, Eric; Kemen, Katherine
Abstract: Objective: Although hospital emergency preparedness efforts have been recognized as important, there has been growing pressure on cost containment, as well as consolidation within the US health care system. There is little data looking at what health care emergency preparedness functions have been, could be, or should be centrally coordinated at a system level. Methods: We developed a questionnaire for academic health systems and asked about program funding, resources provided, governance, and activities. The questionnaire also queried managers' opinions regarding the appropriate role for the system-level resources in emergency response, as well as about what is most helpful at the system-level supporting preparedness. Results: Fifty-two of 97 systems (54%) responded. The most frequently occurring system-wide activities included: creating trainings or exercise templates (75%), promoting preparedness for employees in the system (75%), providing access to specific subject matter experts (73%), and developing specific plans for individual member entities within their system (73%). The top resources provided included a common mass notification system (71%), arranging for centralized contracts for goods and services (71%), and providing subject matter expertise (69%). Conclusions: Currently, there is wide variation in the resources, capabilities, and programs used to support and coordinate system-level emergency preparedness among academic health systems. ( Disaster Med Public Health Preparedness . 2018;12:574–577)